INTENTION TO RECEIVE INFLUENZA VACCINATION AMONG PREVENTIVE MEDICINE STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2024 AND ASSOCIATED FACTORS (Tạp chí Y học Cộng đồng, 2026)
Objective: This study aimed to describe the intention to receive seasonal influenza vaccination among preventive medicine students at Hanoi Medical University in 2024 and to analyze associated factors.Methods: A cross-sectional descriptive study was conducted on 447 preventive medicine students at Hanoi Medical University.Results: Only 66% of students intended to receive the seasonal influenza vaccine. The two main barriers to vaccination were lack of time and concerns about post-vaccination side effects. Female students were 1.6 times more likely to intend to get vaccinated compared to male students (95% CI: 1.1–2.4). Additionally, students who had previously received the influenza vaccine were 6.4 times more likely to intend to get vaccinated in the future than those who had not (95% CI: 3.1–13.1).Conclusion: The proportion of students intending to receive the seasonal influenza vaccine remains low, at only 66%, with significantly lower rates observed among male students and those who have never been vaccinated. Strengthening communication strategies that provide accurate information and emphasize the benefits of vaccination, especially targeting male students and those without prior vaccination, is essential to increase vaccination intention
Keywords: Vaccination intention, seasonal influenza vaccine, medical students